Impacts of agricultural antibiotic exposure on the development and gene expression of Musca domestica - Griese, Herman (My University, 2025)
House flies (Musca domestica L.), common in livestock environments, often develop in substrates containing antibiotic residues from agricultural practices. This study assesses the effects of two widely used antibiotics, tetracycline and enrofloxacin, on larval physiology and gene expression. Developmental assays demonstrated dose-dependent impacts on survival, development time, and individual weights. To explore the molecular basis of these responses, we conducted RNA-seq to profile transcriptional changes in larvae exposed to environmentally relevant and elevated antibiotic concentrations. High concentrations of both antibiotics caused significant transcriptional stress. Tetracycline exposure led to altered mitochondrial and ribosomal pathways, while enrofloxacin broadly disrupted cellular transport and detoxification systems. Both treatments increased expression of detoxification-related genes, suggesting potential cross-resistance mechanisms. These findings reveal that antibiotic residues can significantly influence house fly biology through both physiological and molecular pathways. This study underscores the broader ecological implications of antibiotic use in livestock production, highlighting the need to consider non-target effects on pest species that play roles in disease transmission and resistance evolution.
Keywords: House fly; Antibiotics; Tetracycline; Enrofloxacin; Trancriptomics